Digital Economy Analysis in Driving Economic Growth in Indonesia - Windi Aulia; Wahyu Indah Sari; Dewi Mahrani Rangkuty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a quantitative associative technique to examine how Indonesia's digital economy contributes to economic growth. For the years 2014–2023, secondary data were acquired from the Central Bureau of Statistics, Bank Indonesia, and the World Bank. The Two-Stage Least Square (TSLS) method and a simultaneous model with two equations were used to analyze the impact of monetary variables (interest rates, money supply, and inflation) and digital economy variables (internet users, e-commerce growth, and e-money users) on economic growth. The findings indicate that while e-commerce expansion and inflation have a negligible negative impact on economic growth, internet and e-money users have a large beneficial impact. In the meanwhile, inflation is significantly impacted positively by the money supply and negatively by interest rates and economic growth. These results highlight how crucial it is to manage monetary factors and improve digital infrastructure in order to promote Indonesia's economic growth in the digital age.